2022
DOI: 10.1002/adom.202200255
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Optical Amplification of Waveguide Cut‐Off Mode in Polymer Waveguide Doped with Graphene Quantum Dots

Abstract: (2 of 6)www.advopticalmat.de demonstrate that the GQDs are extremely promising as broadband optical gain media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Further details on these methods will be discussed in section 3.3. 112 When applying GQDs, one of the factors to consider is the wavelength of the PL emitted from GQDs. GQDs can emit PL over a wide range spanning UV, Vis, and NIR regions.…”
Section: Optical Propertymentioning
confidence: 99%
“…Further details on these methods will be discussed in section 3.3. 112 When applying GQDs, one of the factors to consider is the wavelength of the PL emitted from GQDs. GQDs can emit PL over a wide range spanning UV, Vis, and NIR regions.…”
Section: Optical Propertymentioning
confidence: 99%
“…Passivation of GQDs employing materials like PEG, PEI, and benzyl alcohol has been reported [129,130,166]. More recently, studies have even reported enhanced broadband optical amplification through GQDs passivation with polymer matrices [167].…”
Section: Photoluminescence Properties Of Gqdsmentioning
confidence: 99%
“…Actually, the coordination spheres of Nd 3+ should keep stable during device fabrication, and therefore ligands with strong coordination abilities, e.g., β-diketone and phosphine oxide, are desired for enhancing processability. , However, except for a nonprocessable Nd-MOF, all reported Nd 3+ complexes containing β-diketone and phosphine oxide ligands were mononuclear until present. Nd 3+ coordination polymers with well-defined structures were absent, let alone lanthanide coordination polymer-based RDWAs. It is already demonstrated that aromatic ligands can effectively improve absorption ability of the complexes. Especially, rigid phosphine oxide ligands markedly enhanced NIR emissions of mononuclear Nd 3+ complexes through alleviating low-frequency vibration-induced energy loss, in addition to their tunable energy levels well matching with those of primary ligands and Nd 3+ ions. , Nonetheless, with respect to developing high-performance Nd 3+ coordination polymers, excited-state quenching by vibrational de-excitation and interpolymer interactions should be simultaneously suppressed through enhancing both ligand molecular and coordination rigidities.…”
Section: Introductionmentioning
confidence: 99%